Conceito como signo: Elemento semiótico para análise e mediação da informação - Almeida, Carlos Cândido de [UNESP] (My University, 2012)
Knowledge organization promotes advances in theoretical and applied study of concepts. This paper explores the question of semiotic backgrounds of knowledge organization, informational mediation and communication, focusing on the pragmatic-semiotic meaning of concepts. We conclude that organizing information and knowledge approaches that seek to emphasize the meaning of language used by a community must to recognize the semiotic characteristics of concepts.
Concept is a sign: A semiotic element for information mediation and document analysis
Keywords: Concepts; Information mediation; Knowledge Organization; Semiotics; Signs